Pengenalan Coding Bagi Usia Sekolah Menggunakan Aplikasi SHINIBIK (Shinhan University dan IBI Kosgoro 1957) Bagi Murid Sekolah Dasar Negeri 11 Lenteng Agung Jakarta Selatan - Boy Firmansyah; Andri Priawijaya Nur; Filda Angelia; Waskita Cahya; Astried Silvani Akbar (Jurnal Pengabdian Teratai, 2020)
Industrial Era 4.0 brought Indonesian people to a technological mindset that covered various aspects of life. Technology is now open again to luxury things (luxury) so that people can not be separated from the rise of technological facilities. In preparation for entering the industrial era 5.0, there is no doubt that information retrieval is greatly supported and facilitated by various technology-based devices and applications. Information which is currently an important basic material in shaping concrete data makes information important in various aspects of life.Based on the adage "do not know then do not love" will bring every human being will continue to need information that is used to recognize something so that it can more quickly adapt and easily accept the positive things that exist. For this reason, the existence of a computer-based application created by using a specific programming language coding as a tool that can help humans in finding things that can be information for him. Responding to this matter, where there are still so many people who are not familiar with coding, especially in school-age children, we intend to help one of the current government programs, which is helping programs that lead people to better recognize coding, especially at school age.